Pengaruh Model Pembelajaran Contextual Teaching and Learning Berbantuan Kartu Masalah Kemampuan Pemecahan Masalah Siswa Kelas VIII SMP N 2 Kuala Tahun Pelajaran 2016/2017 - Dira Puspita Sari (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
This study aimed to determine the effect of learning model contextual teaching and learning assistanceproblem card of the mathematical problem solving ability of students. Randomly selected two classes as research subjects. Experimental class by learning model contextual teaching and learning assistance problem card with the number 31 and the control class by conventional teaching methods of inquiry that amounted to 30 people.  Based on the results obtained 36,509 4.18296 so that the direction of significant coefficient, 0.94765.76872 then linear, 4,36 1.70 then learning model contextual teaching and learning assistance problem card can impact the ability of students' mathematical problem solving.